The Relationship between Carotid Intima-Media Thickness and Ocular Circulation in Type-2 Diabetes. (20th February 2019) - Ichinohasama, Kohei; Kunikata, Hiroshi; Ito, Azusa; Yasuda, Masayuki; Sawada, Shojiro; Kondo, Keiichi; Satake, Chihiro; Katagiri, Hideki; Nakazawa, Toru
Abstract : Purpose . To compare clinical findings, including ocular blood flow and intima-media thickness (IMT) of the carotid artery, in mild nonproliferative diabetic retinopathy (NPDR) and no diabetic retinopathy (NDR) patients, and to determine risk factors contributing to mild NPDR. Methods . In 129 subjects (129 eyes) with type-2 diabetes patients and mild NPDR or NDR, standard statistical techniques were used to determine associations between clinical findings, including diabetes duration, blood levels of creatinine and hemoglobin A1c (HbA1c), central macular thickness (CMT; measured with optical coherence tomography), mean blur rate (MBR; measured with laser speckle flowgraphy), and ultrasound-measured carotid IMT. Results . Diabetes duration, IMT, and CMT were significantly higher in the mild NPDR patients than the NDR patients (P = 0.004, P = 0.004, andP = 0.003, respectively), while conversely, MBR in the overall optic nerve head (MBR-A) was lower in the mild NPDR patients. Furthermore, a logistic regression analysis showed that diabetes duration (OR, 1.11;P = 0.006 ), diastolic blood pressure (OR, 0.93;P = 0.025 ), heart rate (OR, 1.07;P = 0.004 ), IMT (OR, 8.65;P = 0.005 ), and CMT (OR, 1.03;P = 0.007 ) were independent contributing factors to mild NPDR. Spearman's rank correlation test also showed that IMT was negatively correlated with MBR-A (P = 0.011 ). Conclusions . Increased IMT showed a close association with ocular ischemia in patients with type-2 diabetes and contributed to the presence of mild NPDR. These findings suggest that IMT may be an early biomarker of mild NPDR.